Prevalencia de parasitismo intestinales en niños de jardines del sector Víctor Raúl Haya de la Torre, Virú. (La Libertad, Perú) - Flores Ocaña, Roxana Elizabeth (2018)
Intestinal parasitosis continues to be a public health problem of great importance in Peru, socioeconomic and demographic conditions have a preponderant role. In this sense, the objective of the study was to determine the prevalence of intestinal parasitosis in children of children of the sector Victor Raul Haya de la Torre, Virú. La Libertad, Peru. A total of 197 children from three kindergartens were studied through the methods of direct coproparasitological study and the Graham method. A general prevalence of parasitosis was found of 74% (n = 145). The prevalence by sex was 76% (n = 78) for girls and 71% (n = 67) for boys; according to age, it was 66% (n = 29) for 3 years, 78% (n = 66) for 4 years and 74% (n = 50) for 5 years. The three schools had a prevalence of parasitosis of 70%, 74% and 78% respectively, Entererobius vermicularis 65% (n = 128), Ascaris lumbricoides 16% (n = 32), Echerichia coli sp. 16% (n = 32), Diphyllobothrium pacificum 3% (n = 6), Hymenolepis nana 1.5% (n = 3), Taenia saginata 1% (n = 2) and Strongiloides stercolaris 0.5% (n = 1). It is concluded that in the Víctor Raúl Haya de Torre sector there are three quarters of the studied population are infected by one or more parasitic species